From eLearning to Digital Transformation: A Framework and Implications for L&D - Seufert, Sabine; Meier, Christoph (International Journal of Advanced Corporate Learning (iJAC), 2016)
How can the learning function (L&D) support learning and innovation at the level of an entire organization in times of digital transformation? The core challenges in this are twofold: 1) Competence clarification: What are relevant “digital competences” in terms of knowledge, skills and attitudes that employees need in order to cope with digital transformation? 2) Competence development: How to organize, design and support learning processes contributing to digital competences and digital transformation? Building on a framework originating in the context of business engineering and applying it to corporate training and human resource development, we explicate what digital transformation implies for the L&D function. As L&D functions explore and exploit the options sketched out, they live digital transformation in a way that enables them to effectively and efficiently contribute to digital transformation at an organizational level.